STUDYINGING ORIGINS OF MEDICAL TERMS (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The article is aimed at the history of studying the medical terms as well as illustrating with the brief origin of some specific medical terms. It is recommended to use the written article at medical organizations, as without knowing the main medical terms, it is difficult to be aware of medicine.